2018
DOI: 10.1155/2018/7835676
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Multicenter Study of Workplace Violence against Prehospital Emergency Medical Technicians

Abstract: Background and Purpose Workplace violence is a global phenomenon and violation of human rights affects the people's self-esteem and quality of work and causes inequality, discrimination, disorder, and conflict at work. The present study was carried out aiming at determining the workplace violence against the prehospital emergency medical technicians (PEMTs) in three provinces of Fars, Kohgiluyeh and Boyer-Ahmad, and Bushehr, Iran. Materials and Methods This was a cross-sectional multicenter study in which 206 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
3
24
1
1
Order By: Relevance
“…Specifically, Indian EMTs were more likely to experience physical assault than emergency department workers in Karachi, Pakistan (16.5%) and Johannesburg, South Africa (17%) 1 13 27. While a recent multicenter study of EMTs in Iran revealed rates of physical assault (60.3%) comparable to our Indian study population (58%),14 physical violence among EMTs was less frequent in Saudi Arabia (8.3%), Chile (13.5%) and a prior study from Iran (38%) 14 15 27 28. More than half of our participants also experienced verbal assault (59.8%; 95% CI 54.5% to 65%).…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Specifically, Indian EMTs were more likely to experience physical assault than emergency department workers in Karachi, Pakistan (16.5%) and Johannesburg, South Africa (17%) 1 13 27. While a recent multicenter study of EMTs in Iran revealed rates of physical assault (60.3%) comparable to our Indian study population (58%),14 physical violence among EMTs was less frequent in Saudi Arabia (8.3%), Chile (13.5%) and a prior study from Iran (38%) 14 15 27 28. More than half of our participants also experienced verbal assault (59.8%; 95% CI 54.5% to 65%).…”
Section: Discussionmentioning
confidence: 39%
“…The WHO identified global healthcare providers as particularly vulnerable to WPV, which can substantially affect the welfare and retention of this vital workforce 12. Prior investigations have examined WPV among emergency department and hospital workers in LMICs, but few studies have been conducted on prehospital care providers such as emergency medical technicians (EMTs) 4 13–15. Importantly, violence at the workplace can lead to injuries requiring medical attention and/or leave from work with one study suggesting that 25% of WPV cases lead to injury and 37% require medical care 4 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…One of the findings of the study revealed non‐reaction to workplace violence as one of the common strategies used by the nurses participating in the study. The non‐reaction to workplace violence among pre‐hospital staff is not a new issue, and some studies in the Middle East such as Saudi Arabia (EMTs) (Alharthy et al, ) and Iran (EMTs) (Hosseinikia, Zarei, Najafi Kalyani, & Tahamtan, ) confirm this finding. What is important in this study is that the reasons for the non‐reaction to workplace violence were uncovered, which included fears of a deteriorating incident scene, harming the patient and ineffective follow‐up of workplace violence.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, the participants stated that in such cases, they did not enter the incident scene at all and would wait for the police or, if they did, they would immediately leave the scene with or without the patient. Studies in Spain (healthcare professionals including physicians, nurses or emergency care assistants) (Bernaldo‐De‐Quirós, Piccini, Gómez, & Cerdeira, ) and Iran (EMTs) (Hosseinikia et al, ) reported EMS personnel abandoning the patient and escaping the scene. While confirming these findings, this study also highlighted the reasons for using this strategy, primarily to maintain personal safety.…”
Section: Discussionmentioning
confidence: 99%
“…(25) Verbal abuse, similar to the findings of other national and international studies, was the form of violence with the highest prevalence. (9,17,26,27) Different from physical violence, verbal abuse was primarily perpetrated by females, by peers and superiors. Studies conducted in Chile showed the same findings, and attributed the high occurrence of verbal abuse to the abuser's mild or absent punishment.…”
Section: Discussionmentioning
confidence: 99%